A STUDY OF THE CHANGING FACE OF FAMILY LIFE IN INDIAN - Leela Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Families are always evolving, and experts in today's society argue that today's families are not the same as they once were and that members of today's families "often tinged with sorrow for a healthier past" (Allan, G., Crow, G. & Hawker, S., 2011 p. 1). Alterations were also made to India's traditional family structure. The changes taking place and the interventions being carried out are becoming more and further apart. The primary goal of replies from the social work field should be to close this gap. There are many different models, each of which is extremely helpful in responding to the requirements of evolving families. Indian families still believe in the importance of keeping closeness and emotional connectivity between kith and kin despite the dramatic changes that have occurred in the traditional structure of the family. In light of this, initiatives are being taken by organizations and experts to enhance the link that exists among family members. In spite of the fact that India has the world's lowest divorce rate, occurring in only one out of every hundred marriages, the most recent data and research show that divorce and separation are becoming more common in India. The primary focus of the professional social workers is to foster healthy and productive relationships among the many members of the evolving families they serve. S. P. Rajeev, 2014). However, the fast shifts that are taking place in the responsibilities and activities of the family are something that professional interventions must never ignore